2002
DOI: 10.1097/00002508-200209000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Lidocaine Patch 5% Effectively Treats All Neuropathic Pain Qualities: Results of a Randomized, Double-Blind, Vehicle-Controlled, 3-Week Efficacy Study With Use of the Neuropathic Pain Scale

Abstract: This study demonstrates that LP reduces the intensity of all common neuropathic pain qualities and thus may be of potential benefit for nonallodynic neuropathic pain states. Furthermore, these findings suggest that peripheral mechanisms may play a role in the pathophysiological development of pain qualities that heretofore have been assumed not to involve peripheral mechanisms, such as "dull," "deep," "sharp," and "burning" pains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(132 citation statements)
references
References 7 publications
0
126
0
6
Order By: Relevance
“…Several studies have reported that systemic administration of lidocaine decreases ectopic activity recorded from injured peripheral sensory fibers (Chabal et al, 1989;Devor et al,1992;Omana-Zapata et al,1997a;Sotgiu et al, 1992) and reduces neuropathic pain (Brochu et al, 2006;Erichsen et al, 2003;Sinnott et al, 1999;Smith et al, 2002). Furthermore, systematic reviews of human studies using systemic administration of local anesthetic drugs support their use for neuropathic pain (Kalso et al, 1998) and, in addition, topical or local administration of antidepressants (Lynch et al, 2005;McCleane, 2000) and local anesthetics (Abram, 2000;Galer et al, 1999;Galer, 2002;Galer et al, 2002;Herrmann et al, 2005;Khaliq et al, 2007;Koltzenburg et al, 1994;Meier et al, 2003;Nystrom and Hagbarth, 1981;Roganovic and Mandic-Gajic, 2006;Rowbotham et al, 1996;Varrassi et al, 2006;Vranken et al, 2002) have been demonstrated to be effective in treating neuropathic pain in controlled clinical trials.…”
Section: Contribution Of Peripheral Drive To Spontaneous Activity Of mentioning
confidence: 99%
“…Several studies have reported that systemic administration of lidocaine decreases ectopic activity recorded from injured peripheral sensory fibers (Chabal et al, 1989;Devor et al,1992;Omana-Zapata et al,1997a;Sotgiu et al, 1992) and reduces neuropathic pain (Brochu et al, 2006;Erichsen et al, 2003;Sinnott et al, 1999;Smith et al, 2002). Furthermore, systematic reviews of human studies using systemic administration of local anesthetic drugs support their use for neuropathic pain (Kalso et al, 1998) and, in addition, topical or local administration of antidepressants (Lynch et al, 2005;McCleane, 2000) and local anesthetics (Abram, 2000;Galer et al, 1999;Galer, 2002;Galer et al, 2002;Herrmann et al, 2005;Khaliq et al, 2007;Koltzenburg et al, 1994;Meier et al, 2003;Nystrom and Hagbarth, 1981;Roganovic and Mandic-Gajic, 2006;Rowbotham et al, 1996;Varrassi et al, 2006;Vranken et al, 2002) have been demonstrated to be effective in treating neuropathic pain in controlled clinical trials.…”
Section: Contribution Of Peripheral Drive To Spontaneous Activity Of mentioning
confidence: 99%
“…These plasma levels range from 0.13 to 0.23 μg/ml [259,260], which is approximately one-tenth of the effective level obtained with IVLT. Despite this, neuropathic pain patients achieve pain relief from topical lidocaine [259,[261][262][263][264][265][266][267]. Lidocaine patches also produce analgesia in patients with painful diabetic neuropathy [268], Complex regional pain syndrome (CRPS) [269] and non-neuropathic conditions such as osteoarthritis and low-back pain [261,[270][271][272][273].…”
Section: The Use Of Topical Lidocaine Therapy In Paediatric Chronic Painmentioning
confidence: 99%
“…Long-term pain relief has been observed in clinical trials when lidocaine treatment was started within 2-3 weeks of post-herpetic neuralgia. [24] 2% lidocaine hydrochloride is also indicated for symptomatic relief of irritated or inflamed oral mucosa and pharynx. It is also useful for reducing gagging reflex during intraoral radiographic procedures and making dental impressions.…”
Section: Lidocainementioning
confidence: 99%